Analisis Tingkat Efisiensi Kinerja Keuangan Bank Umum Syariah di Indonesia Pendekatan Data Envelopment Analysis (Periode Tahun 2020-2024) - Jovan Baihaqi Irwan Putra; Cupian Cupian; Nurul Rahmah Kusuma (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study aims to analyze the level of efficiency of the financial performance of Islamic commercial banks in Indonesia using the Data Envelopment Analysis (DEA) method. This study uses a purposive sampling method and uses secondary data in the form of input and output variables from 2020 to 2024 at 10 selected Islamic Commercial Banks (BUS). Data processing was carried out using MaxDEA 12.2 software. The results of the study show that the average annual efficiency level is relatively stable, ranging from 0.773 to 0.817. 2023 recorded the highest average efficiency level, indicating an increase in input management in most banks. Conversely, 2022 was the period with the lowest efficiency, which was likely due to increasing inefficiency or less than optimal utilization of resources in that year. Individually, only Bank Panin Dubai Syariah, Bank Syariah Bukopin, and BTPN Syariah emerged as the banks with the most efficient performance, marked by efficiency scores approaching or reaching 1 in almost all years of the study.